REPUBLIC OF KOREA FOREIGN POLICIES AND UNITED STATES REACTIONS: THE CASES OF THE TWO NORDPOLITIKS - Chu, Mijung (Monterey, CA; Naval Postgraduate School, 2021)
This thesis studies the influence of the United States on the Republic of Korea’s Nordpolitik and Neo-Nordpolitik policies, and the interaction between the ROK and the United States in the process of executing the two policies. The Neo-Nordpolitik policy is a foreign and unification policy currently being pursued by the Moon Jae-in government in South Korea, subsequent to the Nordpolitik policy of the Roh Tae-woo administration in the early 1990s. This thesis focuses in-depth on the practical role the United States played in the process of promoting and implementing the two policies. The research for this thesis finds that the United States treated the ROK largely with consistency and consideration over the period spanning these two policies but behaved quite differently toward the two policies themselves. The United States, directly and indirectly, took a supportive position regarding the Nordpolitik policy. On the contrary, the United States, in an indirect manner, has effectively taken a divergent position regarding the Neo-Nordpolitik policy. The thesis explains the different responses of the United States in terms of the two policies’ alignments with U.S. interests in the overall circumstances in the Northeast Asia region, which was strong in the first case but is weak in the current case. Approved for public release. Distribution is unlimited. Outstanding Thesis So-ryeong, Republic of Korea Air Force